Human Rights from a Social Accounting Perspective in a Post-conflict Environment: The Case of Sri Lanka - Pavithra Siriwardhane; Prem W.S. Yapa (Australasian Accounting, Business and Finance Journal, 2021)
This paper examines how three decades of civil conflict in Sri Lanka has impacted the perceptions of the accounting practitioners with regard to human rights (both during and post-conflict). Using the legitimacy lens in social accounting and the role of the state-supported accountancy body - Institute of Chartered Accountants Sr Lanka (CASL) human rights case is investigated. Specifically, the study’s scope is on rights and the degree of legitimacy formation for which accounting associations are accountable for human rights disclosure in a post-conflict environment in an emerging economy. The study interprets documentary evidence and a survey data that was administered among the members of the CASL. The findings reveal that the civil conflict had not hindered the accountants being in parallel with the legitimacy of social accounting notions adopted by the Western world in the disclosure of human rights. At the individual response level, they perceive that the accounting discipline as agents to promote human rights disclosure in business entities. Despite the fact, that this study has a low response rate, what is generalisable is an understanding of the processes and mechanisms which relate to the way the accountants perceived human rights by themselves. The practical implication indicates that urgent measures need to be undertaken to mainstream the legitimate human rights obligations of business entities since there is no one-size-fits-all strategy in a post-conflict environment. The social implication is that awareness of human rights issues, especially among the next generation of accountants is vital since this transformation would enable them not only to be technically competent but also to be ethical in a post-conflict environment. The study contributes to the literature on perceptions of human rights in a post-conflict environment from a social accounting perspective in an emerging economy.
Keywords: Chartered accountants; Human rights; Institute of Chartered Accountants of Sri Lanka; Legitimacy; Post-conflict environment; Social accounting